Can Uncertainty Improve Promotions? - Goldsmith, Kelly; Amir, On (Journal of Marketing Research, 2010)
Many consumer promotions involve uncertainty (e.g., purchase incentives offering the chance to receive one of several rewards). Despite retailers’ heavy reliance on such promotions, much academic research on uncertainty has demonstrated examples of consumers avoiding and/or disliking uncertainty, implying that promotions involving uncertainty may not be as effective for retailers as promotions offering certain rewards. In an effort to reconcile the prevalence of uncertain promotions with the existing research, this article explores the conditions under which uncertain promotions may be effective for retailers. The article concludes with a discussion of the theoretical and practical implications for these findings.